(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Allergic diseases and bronchial asthma in children are increasingly recognized as significant global health concerns due to their rising prevalence and impact on quality of life. Pediatric allergic conditions, including atopic dermatitis, allergic rhinitis, and food allergies, often coexist and may predispose children to bronchial asthma. Environmental factors, genetic predisposition, and early-life exposures play a crucial role in disease onset and progression. Bronchial asthma is characterized by chronic airway inflammation, reversible airflow obstruction, and recurrent episodes of wheezing, coughing, and shortness of breath. Effective management requires early diagnosis, identification of triggers, appropriate pharmacotherapy, and patient education to reduce morbidity and prevent long-term complications. Recent studies emphasize immunological mechanisms, environmental control, and personalized treatment strategies for better clinical outcomes [1, 2].